Evaluasi Usability Aplikasi Absensi Digital Pada Badan Pusat Statistik Kabupaten Manokwari Menggunakan Metode System Usability Scale: Evaluasi Usability Aplikasi Absensi Digital Pada Badan Pusat Statistik Kabupaten Manokwari Menggunakan Metode System Usability Scale - Josua Josen A. Limbong; Duta Rael Bintang Pratama (JISTECH: Journal of Information Science and Technology, 2025)
The development of information technology has encouraged the digitization of employee attendance systems, including at the Central Bureau of Statistics (BPS) Manokwari which implements a fingerprint-based digital attendance application. Although it aims to improve the efficiency and accuracy of attendance recording, this application still faces various obstacles, such as dependence on internet connection, less than optimal interface display, and compatibility issues with user devices. This study aims to evaluate the usability level of the BPS Manokwari digital attendance application using the System Usability Scale (SUS) method. This method is used to measure aspects of learnability, efficiency, memorability, errors, and satisfaction based on user experience. This study involved 35 respondents who were permanent employees of BPS Manokwari. Data was collected through SUS questionnaire, then analyzed using SPSS software. The evaluation results show that the digital attendance application obtained a score of 68.42 in SUS, which falls into the Marginal High category. Although this application has functioned to meet the needs of employees, there is still significant room for improvement to achieve higher usability quality, especially in the aspects of ease of use and interface appearance. Based on the results of the analysis, this research provides recommendations for improvement to increase efficiency and user comfort in accessing the application